A high-hardness transparent conductive glass product and a method for manufacturing the same

CN122991722APending Publication Date: 2026-10-27SUZHOU SYNMINWAY NANO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611352285.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是,碳纳米管容易在液相中缠结和团聚,碳纳米管含量过低时难以形成连续导电通路,含量过高时又容易造成透光率下降和雾度升高

Benefits of technology

(1)本发明通过聚硅氮烷树脂形成含硅无机相,并与有机树脂相共同固定碳纳米管导电网络,有利于提高复合涂层与玻璃基材之间的结合稳定性、膜层完整性及表面硬度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991722A_ABST
    Figure CN122991722A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of functional glass, in particular to a high-hardness transparent conductive glass product and a preparation method thereof. The glass product comprises a glass substrate and a carbon nanotube composite coating directly combined with the surface of the glass substrate, the composite coating comprises a silicon-containing inorganic phase formed by curing a polysilazane resin, an organic resin phase formed by a polyurethane-modified acrylate, an epoxy acrylate and a silicone resin, and a carbon nanotube conductive network formed by mutual lapping of single-walled carbon nanotubes and multi-walled carbon nanotubes. During preparation, the composite coating is formed through grinding, first ultrasonic dispersion, centrifugation, second ultrasonic dispersion after adding a film-forming agent and an auxiliary agent, coating, surface drying and heating curing. The prepared glass product has a light transmittance retention rate of no less than 98%, a haze of no more than 1%, a square resistance of no more than 9*10 6 Ω / □, and a pencil hardness of no less than 3H measured under a load of 750 g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional glass technology, specifically to a high-hardness transparent conductive glass product and its preparation method. Background Technology

[0002] Transparent conductive films possess both optical transmittance and electrical conductivity, making them suitable for applications in displays, antistatic glass, instrument panels, and transparent protective components. Existing transparent conductive films primarily include metal oxide films, conductive polymer films, and carbon nanomaterial films. Metal oxide films typically require vacuum deposition or magnetron sputtering processes, which are costly and result in brittle films; conductive polymer films, on the other hand, suffer from insufficient surface hardness, abrasion resistance, and long-term stability.

[0003] Carbon nanotubes possess a high aspect ratio and excellent electrical conductivity, enabling the formation of conductive networks on transparent substrates through solution coating. However, carbon nanotubes are prone to entanglement and aggregation in the liquid phase. Insufficient carbon nanotube content hinders the formation of continuous conductive pathways, while excessive content leads to decreased light transmittance and increased haze. Furthermore, conventional organic resin-based carbon nanotube coatings often struggle to balance surface hardness, conductive network continuity, and bonding stability with the glass substrate.

[0004] Therefore, it is necessary to provide a carbon nanotube composite coating suitable for glass substrates that can improve the surface hardness of the coating and the bonding stability between the coating and the glass substrate while maintaining high light transmittance, low haze and stable conductivity. Summary of the Invention

[0005] To achieve the above objectives, the present invention provides a high-hardness transparent conductive glass product, comprising a glass substrate and a carbon nanotube composite coating directly bonded to at least one surface of the glass substrate. The carbon nanotube composite coating comprises a silicon-containing inorganic phase, an organic resin phase, and a carbon nanotube conductive network. The silicon-containing inorganic phase is formed by curing polysilazane resin and is bonded to the surface of the glass substrate; The organic resin phase is formed from polyurethane-modified acrylate, epoxy acrylate, and silicone resin; The conductive network of carbon nanotubes includes single-walled carbon nanotubes and multi-walled carbon nanotubes, which overlap to form conductive pathways. A silicon-containing inorganic phase and an organic resin phase are used to immobilize a carbon nanotube conductive network.

[0006] Explanation: The above technical solution uses a silicon-containing inorganic phase, an organic resin phase, and a carbon nanotube conductive network to form a composite coating. The silicon-containing inorganic phase helps to improve the bonding stability between the coating and the glass substrate. The organic resin phase is used to form a continuous film and fix the carbon nanotube conductive network. Single-walled carbon nanotubes and multi-walled carbon nanotubes overlap to form conductive pathways, thereby taking into account the coating's conductivity, film-forming properties, and surface hardness.

[0007] Furthermore, the mass ratio of polyurethane modified acrylate, polysilazane resin, epoxy acrylate and silicone resin, based on the mass of the resin stock solution, is (8-12):(12-15):5:3; the silicone resin is a polyorganosiloxane with a cross-linked network structure.

[0008] Note: The above film-forming component ratio can coordinate the hardness and interfacial bonding ability of the silicon-containing inorganic phase with the continuous film formation and stress buffering ability of the organic resin phase, so that different film-forming components can synergistically fix the carbon nanotube conductive network, which is beneficial to improving the structural integrity and stability of the composite coating.

[0009] Furthermore, the mass ratio of single-walled carbon nanotubes to multi-walled carbon nanotubes is 3–5:1; the diameter of single-walled carbon nanotubes is 1–3 nm, and the diameter of multi-walled carbon nanotubes is 5–30 nm.

[0010] Note: The above-mentioned single-walled carbon nanotubes and multi-walled carbon nanotubes are used in combination according to a limited ratio and diameter range, so that carbon nanotubes of different sizes can overlap to form a continuous conductive path, while taking into account the uniformity and mechanical stability of the conductive network.

[0011] Furthermore, no separate organic undercoat is placed between the glass substrate and the carbon nanotube composite coating, and the dry film thickness of the carbon nanotube composite coating is 2–4 μm.

[0012] Note: The carbon nanotube composite coating is formed directly on the surface of the glass substrate, which can reduce the additional processes and interlayer interfaces caused by the independent organic base coating; controlling the dry film thickness within the above range is beneficial to balance the continuity of the film, transparency and the stability of the conductive network.

[0013] Furthermore, the high-hardness transparent conductive glass product retains a light transmittance of no less than 98% relative to the uncoated glass substrate, a haze of no more than 1%, and a sheet resistance of no more than 9 × 10⁻⁶. 6 Ω / □, and the pencil hardness measured under a 750 g load is not less than 3 H.

[0014] Note: The above performance range defines the overall performance of glass products in terms of transparency, haze, conductivity and surface hardness, so that the composite coating can maintain high optical transmittance while having stable conductivity and high surface hardness.

[0015] In another aspect, a method for preparing a high-hardness transparent conductive glass product is also provided, comprising the following steps: S1. Mix and grind single-walled carbon nanotubes and multi-walled carbon nanotubes. Add the ground carbon nanotube material and dispersant to deionized water for the first ultrasonic dispersion. Then centrifuge and collect the supernatant to obtain carbon nanotube dispersion. S2. Add film-forming agent and additives to carbon nanotube dispersion and perform a second ultrasonic dispersion to obtain aqueous carbon nanotube coating solution; The film-forming agents include polyurethane-modified acrylates, polysilazane resins, epoxy acrylates, and silicone resins. S3. Apply the aqueous carbon nanotube coating solution directly to at least one side of the glass substrate to form a wet film; S4. After the wet film is surface dry, it is heated and cured to form a silicon-containing inorganic phase of polysilazane resin, and an organic resin phase of polyurethane-modified acrylate, epoxy acrylate and organosilicon resin. The silicon-containing inorganic phase and the organic resin phase together fix the carbon nanotube conductive network formed by single-walled carbon nanotubes and multi-walled carbon nanotubes, forming a carbon nanotube composite coating on the surface of the glass substrate, and obtaining a high-hardness transparent conductive glass product.

[0016] Explanation: The preparation method first obtains a uniform carbon nanotube dispersion by grinding, first ultrasonic dispersion and centrifugation, and then mixes the carbon nanotubes with the film-forming agent and additives by second ultrasonic dispersion. Subsequently, the mixture is directly coated, surface dried and heated to form a silicon-containing inorganic phase, an organic resin phase and a carbon nanotube conductive network, thereby obtaining a structurally stable transparent conductive composite coating.

[0017] Furthermore, in S1, the mass ratio of single-walled carbon nanotubes to multi-walled carbon nanotubes is 3 to 5:1; The raw materials of the carbon nanotube dispersion include, by mass percentage, 0.01% to 1.5% carbon nanotube material, 0.1% to 8.5% dispersant, and the balance being deionized water; The grinding time is 3 to 8 hours, the power of the first ultrasonic dispersion is 250 to 400 W, and the time of the first ultrasonic dispersion is 15 to 60 minutes.

[0018] Note: The above-mentioned carbon nanotube dosage, dispersant dosage, and grinding and first ultrasonic dispersion conditions can promote the uniform dispersion of single-walled and multi-walled carbon nanotubes. Centrifugation removes insufficiently dispersed agglomerates, which helps to reduce the adverse effects of carbon nanotube agglomeration on subsequent film uniformity and optical properties.

[0019] Furthermore, in S2, the additives include wetting agents, leveling agents, defoamers, and thickeners; based on the mass of the carbon nanotube dispersion, the amount of film-forming agent added is 10%–40% of the mass of the carbon nanotube dispersion, the amount of wetting agent added is 0.1%–1.8%, the amount of leveling agent added is 0.05%–0.6%, the amount of defoamer added is 0.01%–0.3%, and the amount of thickener added is 0.05%–0.1%. The mass ratio of polyurethane modified acrylate, polysilazane resin, epoxy acrylate and silicone resin, based on the mass of the resin stock solution, is (8-12):(12-15):5:3; The power of the second ultrasonic dispersion is 250-400 W, and the time of the second ultrasonic dispersion is 15-30 min.

[0020] Note: The above-mentioned film-forming agent and additives can enable the carbon nanotube dispersion system to have suitable film-forming properties, wettability, leveling and viscosity. The secondary agglomeration generated after the addition of film-forming components is reduced by the second ultrasonic dispersion, which is conducive to the formation of a continuous and uniform composite coating.

[0021] Furthermore, the aforementioned wetting agent is an anionic modified polyether silicone wetting agent or an alkyl sulfonate wetting agent; The leveling agent includes at least two silicone-based leveling agents; The defoamer is a silicone-based defoamer or a polyether-modified silicone-based defoamer; The thickener is an aqueous thickener of polyacrylate or sodium polyacrylate.

[0022] Note: The above-mentioned wetting agents, leveling agents, defoamers and thickeners, when used in combination with the aqueous carbon nanotube system, can respectively improve the wetting and spreading properties of the coating liquid, wet film leveling, bubble elimination and anti-settling properties, thereby improving the stability of the coating process and the uniformity of the cured film.

[0023] Furthermore, in S1, based on the total mass of the raw materials used to prepare the carbon nanotube dispersion, the mass percentage of carbon nanotube material is 0.5%, the mass percentage of dispersant is 5%, the mass ratio of single-walled carbon nanotubes to multi-walled carbon nanotubes is 4:1, the grinding time is 6 h, the power of the first ultrasonic dispersion is 360 W, and the time of the first ultrasonic dispersion is 45 min. In S2, based on the mass of the carbon nanotube dispersion, the amount of film-forming agent added was 35%, the amount of wetting agent added was 1%, the amount of leveling agent added was 0.3%, the amount of defoamer added was 0.15%, the amount of thickener added was 0.05%, the power of the second ultrasonic dispersion was 360 W, and the time of the second ultrasonic dispersion was 30 min. In S3, the thickness of the wet film is 6 μm; In S4, the wet film is surface-dried at 25°C for 5 min, and then cured at 80~120°C for 10~45 min to form a carbon nanotube composite coating. The dry film thickness of the carbon nanotube composite coating is 2~4 μm.

[0024] Note: The above-mentioned optimized process parameters enable carbon nanotubes to maintain good dispersion and overlap, and ensure thorough mixing of the film-forming agent and various additives. By controlling the wet film thickness, surface drying conditions, and curing conditions, the coating is fully shaped and cured, thereby forming a carbon nanotube composite coating with uniform thickness, stable structure, and good transparency, conductivity, and surface hardness.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention forms a silicon-containing inorganic phase through polysilazane resin and fixes the carbon nanotube conductive network together with the organic resin phase, which is beneficial to improving the bonding stability, film integrity and surface hardness between the composite coating and the glass substrate.

[0026] (2) The present invention uses single-walled carbon nanotubes and multi-walled carbon nanotubes to form a conductive path, which is beneficial to construct a uniform and stable carbon nanotube conductive network, and takes into account the conductivity and transparency of the coating.

[0027] (3) The present invention uses grinding, two ultrasonic dispersions and centrifugation, and with the addition of wetting agent, leveling agent, defoamer and thickener, which helps to reduce carbon nanotube agglomeration and coating defects, and improve the dispersion stability and film uniformity of the coating liquid.

[0028] (4) The glass products made by the present invention can take into account high light transmittance, low haze, stable sheet resistance and high pencil hardness, and are suitable for glass products with comprehensive requirements for transparency, conductivity and surface mechanical properties. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of the structure of the high-hardness transparent conductive glass product of the present invention; In the figure, 1-glass substrate, 2-carbon nanotube composite coating, 21-silicon-containing inorganic phase, 22-organic resin phase, 23-carbon nanotube conductive network, 231-single-walled carbon nanotube, 232-multi-walled carbon nanotube; Figure 2 This is a flowchart of the method for preparing high-hardness transparent conductive glass according to the present invention; Figure 3 This is an appearance diagram of the high-hardness transparent conductive glass product prepared according to the present invention. Detailed Implementation

[0030] The present invention will be further described below with reference to specific embodiments and experimental examples. The following embodiments are used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention.

[0031] Unless otherwise specified, the amounts of carbon nanotube material, dispersant, and deionized water in S1 are based on the total mass of all raw materials used to prepare the carbon nanotube dispersion system before centrifugation; the amounts of film-forming agent, wetting agent, leveling agent, defoamer, and thickener added in S2 are based on the mass of the carbon nanotube dispersion obtained after centrifugation and collection in S1. For example, an addition of 35% film-forming agent means that 35 parts by mass of film-forming agent are added to every 100 parts by mass of carbon nanotube dispersion, without adding water or other solvents to make the total volume of the final coating liquid equal to 100 parts by mass.

[0032] The film-forming agents include polyurethane modified acrylate, polysilazane resin, epoxy acrylate and silicone resin. The mass ratios of the four resins are calculated based on the actual mass of each resin stock solution added.

[0033] The glass substrate used in the following embodiments is soda-lime transparent glass with dimensions of 100 mm × 100 mm × 2 mm.

[0034] Single-walled carbon nanotubes are selected from products with a diameter of 1–3 nm, a length greater than 30 μm, and a purity of not less than 99%; multi-walled carbon nanotubes are selected from products with a diameter of 5–30 nm, a length of 10–20 μm, and a purity of not less than 98.5%. The above specifications are the range of raw material specifications and are not intended as actual average parameters in a single embodiment.

[0035] The dispersant used is a modified polyvinylpyrrolidone water-dispersible product with a solid content of approximately 30%.

[0036] The polyurethane-modified acrylate uses DH-JZ002 with a solid content of 100%; the polysilazane resin uses JG-1717 produced by Polysilicon High-Tech (Shenzhen) Co., Ltd. with a solid content of 100%; the epoxy acrylate uses SM6140 with a solid content of 100%; and the silicone resin uses a polyorganosiloxane with a cross-linked network structure, specifically Wacker's waterborne silicone resin SILRES® MP50E with a solid content of 50±2%.

[0037] The glass substrate is first cleaned with a neutral detergent to remove surface oil and particles, then cleaned sequentially with deionized water and anhydrous ethanol, and subsequently dried at 60°C for 10 minutes. No separate organic primer is applied to the glass substrate surface before coating.

[0038] Carbon nanotubes were ground using a high-speed stirred vertical mill XD-E750 at a grinding speed of 3000 r / min. The grinding media consisted of zirconia grinding beads with an average particle size of 0.5 mm.

[0039] The aqueous carbon nanotube coating solution was applied to the surface of a glass substrate using a blade coating method. The wet film thickness was 6 μm. After surface drying at 25°C for 5 min, the wet film was heat-cured at 80–120°C for 10–45 min. The dry film thickness of the cured carbon nanotube composite coating was 2–4 μm. Each embodiment used a specific curing temperature and time within the above process window.

[0040] Example 1: This example is a preferred embodiment of the present invention, which uses determined parameters to prepare a high-hardness transparent conductive glass product.

[0041] S1, Preparation of carbon nanotube dispersion Single-walled carbon nanotubes with an average diameter of 2 nm and an average length of 35 μm, and multi-walled carbon nanotubes with an average diameter of 10 nm and an average length of 15 μm were selected and mixed at a mass ratio of 4:1.

[0042] The mixed carbon nanotubes were added to a high-speed stirring vertical sand mill XD-E750 and ground at 3000 r / min for 6 hours.

[0043] Based on a total mass of 100 parts of all dispersed raw materials before centrifugation, weigh out 0.5 parts of ground carbon nanotube material, 5 parts of modified polyvinylpyrrolidone dispersant, and 94.5 parts of deionized water.

[0044] The above raw materials were mixed and then subjected to a first ultrasonic dispersion at a power of 360 W for 45 min. After the first ultrasonic dispersion was completed, the mixture was centrifuged at 3000 r / min for 10 min to remove large carbon nanotube agglomerates that were not fully dispersed. The upper uniform liquid was collected to obtain a carbon nanotube dispersion.

[0045] S2, Preparation of aqueous carbon nanotube coating solution Take 100 parts by weight of the carbon nanotube dispersion obtained from S1, and add 35 parts by weight of film-forming agent, 1 part by weight of wetting agent, 0.3 parts by weight of leveling agent, 0.15 parts by weight of defoamer and 0.05 parts by weight of thickener.

[0046] The film-forming agent is composed of polyurethane modified acrylate DH-JZ002, polysilazane resin JG-1717, epoxy acrylate SM6140 and silicone resin SILRES® MP50E. The mass ratio of the four components based on the mass of the resin stock solution is 10:13:5:3, and the total amount of the four resin stock solutions added is 35 parts by mass.

[0047] The wetting agent used is anionic modified polyether silicone wetting agent SILCO CT1008.

[0048] The leveling agents used are BYK-333 and TEGO Glide 410, which are compounded in a 1:1 mass ratio, and the total amount of the two added is 0.3 parts by mass.

[0049] The defoamers used are TEGO Foamex 840 and BYK-024, which are compounded in a 1:1 mass ratio, and the total amount of the two added is 0.15 parts by mass.

[0050] The thickener used is HY-303, an aqueous polyacrylate thickener, added at a rate of 0.05 parts by weight.

[0051] After all raw materials were added, a second ultrasonic dispersion was performed with an ultrasonic power of 360 W and an ultrasonic time of 30 min to obtain an aqueous carbon nanotube coating solution.

[0052] S3, Coating on the surface of the glass substrate The aqueous carbon nanotube coating liquid obtained in S2 was directly coated onto one side of the cleaned and dried glass substrate, and the wet film thickness was controlled to be 6 μm.

[0053] During the coating process, no independent organic primer is applied between the glass substrate and the wet film.

[0054] S4. Wet film surface drying and heat curing The glass substrate on which the wet film is formed is placed in an environment of 25°C for 5 min to surface dry, and then placed in an oven to cure at 120°C for 20 min.

[0055] After curing, the glass is naturally cooled to room temperature to obtain a high-hardness transparent conductive glass product.

[0056] In this embodiment, the thickness of the cured carbon nanotube composite coating dry film is 3 μm.

[0057] After heat curing, the polysilazane resin forms a silicon-containing inorganic phase; the polyurethane-modified acrylate, epoxy acrylate, and silicone resin together form an organic resin phase. Single-walled carbon nanotubes and multi-walled carbon nanotubes overlap in the composite coating to form a conductive network, which is fixed by the silicon-containing inorganic phase and the organic resin phase.

[0058] The glass products prepared in this embodiment were tested using the method described later. Sheet resistance, transmittance retention, and haze were all measured at nine evenly distributed test points on the same sample. The following ranges represent the measured minimum to maximum values ​​at the nine test points, not the range of process parameters.

[0059] The sheet resistance in this embodiment is 6×10⁻⁶. 5 ~9×10 5Ω / □, transmittance retention rate of 99%~99.6%, haze of 0.5%~0.8%, and pencil hardness of 5 H~6 H measured under a 750 g load.

[0060] Example 2: This example uses another actual process. Except for the following explicit differences, the glass substrate, cleaning method, and basic operating procedures are the same as in Example 1.

[0061] S1, Preparation of carbon nanotube dispersion Single-walled carbon nanotubes with an average diameter of 2 nm and an average length of 35 μm, and multi-walled carbon nanotubes with an average diameter of 18 nm and an average length of 15 μm were selected and mixed at a mass ratio of 3:1.

[0062] The mixed carbon nanotubes were ground at 3000 r / min for 7 h.

[0063] Based on a total mass of 100 parts of all dispersed raw materials before centrifugation, add 0.5 parts by mass of carbon nanotube material, 8 parts by mass of dispersant, and 91.5 parts by mass of deionized water.

[0064] The carbon nanotube dispersion was first ultrasonically dispersed at 360 W for 60 min, followed by centrifugation at 3000 r / min for 10 min. The upper uniform liquid was collected to obtain the carbon nanotube dispersion.

[0065] S2, Preparation of aqueous carbon nanotube coating solution Take 100 parts by weight of carbon nanotube dispersion, and add 25 parts by weight of film-forming agent, 1.5 parts by weight of wetting agent, 0.15 parts by weight of leveling agent, 0.2 parts by weight of defoamer and 0.05 parts by weight of thickener.

[0066] The film-forming agent used was the same four resins as in Example 1, and the mass ratio of the resin stock solution was still 10:13:5:3, with a total addition of 25 parts by mass of the four resin stock solutions.

[0067] The wetting agent used is alkyl sulfonate wetting agent SAS-60.

[0068] The leveling agents used are EFKA3580 and Silsurf®A008, which are compounded at a mass ratio of 1:2, with a total addition amount of 0.15 parts by mass.

[0069] The defoamer used is polyether-modified silicone defoamer BYK-024, and the amount added is 0.2 parts by weight.

[0070] The thickener used is sodium polyacrylate JH-09, and the amount added is 0.05 parts by weight.

[0071] A second ultrasonic dispersion was performed with an ultrasonic power of 360 W and an ultrasonic time of 30 min to obtain an aqueous carbon nanotube coating solution.

[0072] S3, Coating on the surface of the glass substrate The coating liquid was directly applied to one side of the glass substrate using the method described in Example 1, and the wet film thickness was controlled to be 6 μm.

[0073] S4. Wet film surface drying and heat curing The wet film was surface dried at 25°C for 5 min, then cured at 100°C for 20 min, and allowed to cool naturally to room temperature.

[0074] The dry film thickness in this embodiment is 3 μm.

[0075] The sheet resistance of the glass product obtained in this embodiment is 7 × 10⁻⁶. 5 ~9×10 5 The pencil has a transmittance of 98.5%–99.6% and a haze of 0.5%–0.9%, and its hardness is 5H–6H as measured under a 750 g load.

[0076] Example 3: This example provides representative support for the first boundary of the mass ratio of polyurethane modified acrylate, polysilazane resin, epoxy acrylate and silicone resin.

[0077] Except for the mass ratio of the four resin solutions in the film-forming agent being changed from 10:13:5:3 in Example 1 to 8:12:5:3, the other raw materials, carbon nanotube mass ratio, carbon nanotube addition amount, dispersant addition amount, grinding time, two ultrasonic conditions, additive type and addition amount, wet film thickness, surface drying conditions, and curing conditions are all the same as in Example 1.

[0078] Specifically, single-walled carbon nanotubes with an average diameter of 2 nm and multi-walled carbon nanotubes with an average diameter of 10 nm were used in a mass ratio of 4:1; the amount of carbon nanotube material added was 0.5%, the amount of dispersant added was 5%, and the grinding was carried out for 6 hours; the first ultrasonic power was 360 W and the time was 45 min.

[0079] For every 100 parts by weight of carbon nanotube dispersion, add 35 parts by weight of film-forming agent. The four resin stock solutions are weighed in the ratio of 8:12:5:3. The amount of wetting agent added is 1%, the amount of leveling agent added is 0.3%, the amount of defoamer added is 0.15%, and the amount of thickener added is 0.05%. The second ultrasonic power is 360 W and the time is 30 min.

[0080] A 6 μm wet film was formed by coating, surface-dried at 25°C for 5 min, and then cured at 120°C for 20 min. The dry film thickness in this embodiment is 3 μm.

[0081] Example 4: This example is used to provide representative support for another boundary of the mass ratio of four film-forming resins.

[0082] Except for changing the mass ratio of the four resin stock solutions to 12:15:5:3, all other conditions were the same as in Example 1.

[0083] That is, single-walled carbon nanotubes with an average diameter of 2 nm and multi-walled carbon nanotubes with an average diameter of 10 nm were used in a mass ratio of 4:1; the amount of carbon nanotube material added was 0.5%, the amount of dispersant added was 5%, and the grinding was carried out for 6 hours; the first ultrasonic power was 360 W and the time was 45 min.

[0084] For every 100 parts by weight of carbon nanotube dispersion, 35 parts by weight of film-forming agent were added. Polyurethane modified acrylate, polysilazane resin, epoxy acrylate and silicone resin stock solutions were prepared in a mass ratio of 12:15:5:3. Other additives and the second ultrasonic conditions were the same as in Example 1.

[0085] A 6 μm wet film was formed by coating, surface drying at 25°C for 5 min, and then curing at 120°C for 20 min. The reference dry film thickness was 3 μm.

[0086] Example 5: This example is used to provide representative support for the upper boundary of a single-walled carbon nanotube to multi-walled carbon nanotube mass ratio of 3 to 5:1.

[0087] Except for the mass ratio of single-walled carbon nanotubes to multi-walled carbon nanotubes being adjusted from 4:1 in Example 1 to 5:1, all other raw materials and process parameters are the same as in Example 1.

[0088] Specifically, single-walled carbon nanotubes with an average diameter of 2 nm and multi-walled carbon nanotubes with an average diameter of 10 nm are used. The total amount of carbon nanotubes added is still 0.5%, and the mass of the two types of carbon nanotubes is redistributed at a ratio of 5:1.

[0089] Carbon nanotubes were ground for 6 hours, with 5% dispersant added. The first ultrasonic treatment was performed at 360 W for 45 min. 35 parts by weight of film-forming agent were added to every 100 parts by weight of carbon nanotube dispersion. The mass ratio of the four resins was 10:13:5:3. The amount of each additive and the conditions for the second ultrasonic treatment were the same as in Example 1.

[0090] A 6 μm wet film was surface-dried at 25°C for 5 min and then cured at 120°C for 20 min. The reference dry film thickness was 3 μm.

[0091] Comparative Example 1: Except for the carbon nanotube material, which uses only single-walled carbon nanotubes with an average diameter of 2 nm, the other raw materials and process conditions are the same as in Example 1.

[0092] The total amount of carbon nanotube material added remains at 0.5%, meaning that the total amount of carbon nanotubes added is not changed by eliminating multi-walled carbon nanotubes.

[0093] Comparative Example 2: Except that no wetting agent, leveling agent, defoamer and thickener were added in S2, all other conditions were the same as in Example 1.

[0094] To keep the liquid addition amounts in the control system as close as possible, 1.5 parts by weight of deionized water were used to replace the total 1.5 parts by weight of wetting agent, leveling agent, defoamer and thickener in Example 1.

[0095] Comparative Example 3: Except for S4, which did not undergo heating and curing at 120°C, all other conditions were the same as in Example 1.

[0096] After the wet film is surface-dried at 25°C for 5 minutes, it is placed in an environment of 25°C and 50% relative humidity for 24 hours to allow the film to dry at room temperature.

[0097] Comparative Example 4: Except for the absence of polysilazane resin JG-1717 in the film-forming agent and the substitution with an equal mass of polyurethane-modified acrylate DH-JZ002, all other conditions were the same as in Example 1.

[0098] The total amount of film-forming agent added remains at 35 parts by mass per 100 parts by mass of carbon nanotube dispersion.

[0099] Comparative Example 5: Except for the use of polysilazane resin JG-1717 as the film-forming agent, all other conditions were the same as in Example 1.

[0100] For every 100 parts by weight of carbon nanotube dispersion, add 35 parts by weight of polysilazane resin, without adding polyurethane-modified acrylate, epoxy acrylate, or silicone resin.

[0101] Experimental Example 1: Optical, electrical and hardness tests.

[0102] Sheet resistance, light transmittance retention, haze, and pencil hardness were tested on the glass products prepared in Examples 1, 2, and Comparative Examples 1-3, respectively.

[0103] Sheet resistance was measured using an RTS-8 four-probe tester. Nine test points were evenly selected on the surface of each sample, and the sheet resistance at each test point was recorded. The minimum and maximum values ​​among the nine test values ​​were used to represent the spatial test range of the same sample.

[0104] Light transmittance and haze were measured using a conventional haze transmittance tester with a wavelength range of 380–700 nm. Glass substrates of the same batch and specifications but without carbon nanotube composite coatings were used as transmittance references.

[0105] In this invention, the transmittance retention rate indicates the degree to which the transmittance of the coated glass sample is maintained relative to the transmittance of the uncoated glass substrate in the same batch.

[0106] The hardness of the pencil was tested using a pencil hardness tester with a test load of 750 g.

[0107] The test results are shown in the table below.

[0108] Example 1 <![CDATA[6×10 5 ~9×10 5 ]]> 99.0~99.6 0.5~0.8 5~6 Example 2 <![CDATA[7×10 5 ~9×10 5 ]]> 98.5~99.6 0.5~0.9 5~6 Comparative Example 1 <![CDATA[3×10 5 ~6×10 5 ]]> 99.0~99.8 0.7~1 5~6 Comparative Example 2 <![CDATA[8×10 5 ~1.5×10 6 ]]> 98~99.0 0.6~1 4~6 Comparative Example 3 <![CDATA[8×10 5 ~9.5×10 5 ]]> 98.5~99.6 1~1.6 2~3 Both Example 1 and Example 2 have high light transmittance retention, low haze, and pencil hardness of 5H to 6H.

[0109] In Comparative Example 2, without the addition of wetting agents, leveling agents, defoamers, and thickeners, the overall sheet resistance increased, indicating that the addition of additives is beneficial to improving the dispersion, spreading, and film uniformity of the carbon nanotube coating liquid.

[0110] Comparative Example 3, without heat curing, showed that the haze increased to 1%–1.6% and the pencil hardness decreased to 2H–3H, indicating that heat curing is beneficial for forming a stable composite film structure and improving the film hardness and optical uniformity.

[0111] In Comparative Example 1, when only single-walled carbon nanotubes were used, the initial sheet resistance was lower than that of Example 1, and the transmittance retention was also no lower than that of Example 1. Therefore, the experimental data in this example cannot be used to prove that the combination of single-walled and multi-walled carbon nanotubes can reduce the initial sheet resistance or increase the initial transmittance. The technical effect of the two carbon nanotube combinations is mainly judged in conjunction with the conductivity retention performance after friction in Experimental Example 2.

[0112] Experimental Example 2: Organic-inorganic composite film formation and wear resistance and electrical conductivity stability test.

[0113] To verify the effect of the combined action of silicon-containing inorganic phase and organic resin phase on glass interface bonding, coating integrity and electrical conductivity stability after friction, adhesion, pencil hardness and sheet resistance before and after friction were tested for Example 1, Comparative Example 1, Comparative Example 4 and Comparative Example 5, respectively.

[0114] Adhesion was tested using the cross-cut adhesion test. For films with a thickness of 2–4 μm and a cross-cut spacing of 1 mm, 3M 600 transparent test tape with a width of approximately 19 mm was applied, peeled off, and then used for rating.

[0115] The wear resistance test was conducted using a conventional reciprocating wear resistance equipment, with a test load of 500 g and 100 cycles of reciprocating friction. 0000 steel wool was used as the reference friction medium.

[0116] The sheet resistance was measured before and after friction. The rate of change of sheet resistance was calculated as follows: (sheet resistance after friction minus sheet resistance before friction, then divided by sheet resistance before friction and multiplied by 100%). The test results are shown in the table below.

[0117] Example 1 Level 0 5~6 No obvious peeling, few scratches ≤15 Comparative Example 1 Level 1 5~6 Continuous scratches ≥50 Comparative Example 4 Level 2 3~4 Localized peeling ≥70 Comparative Example 5 Level 0-1 5~6 Brittle or fine cracks appear ≥60 Example 1 uses polysilazane resin, polyurethane-modified acrylate, epoxy acrylate, and silicone resin. Compared with Comparative Example 4, Example 1 exhibits higher adhesion stability and surface hardness, and the change in sheet resistance after friction is significantly reduced, indicating that the silicon-containing inorganic phase formed by the polysilazane resin is beneficial to improving the interfacial bonding and mechanical stability of the composite coating.

[0118] Compared with Comparative Example 5, Example 1 can avoid the more obvious brittle cracking phenomenon when only polysilazane resin is used, and has a lower rate of change of sheet resistance after friction, indicating that the organic resin phase can maintain the continuity of the film and provide stable fixation for the carbon nanotube conductive network.

[0119] A comparison of Example 1 and Comparative Example 1 shows that the addition of multi-walled carbon nanotubes did not further reduce the initial sheet resistance, but the composite conductive network formed by single-walled and multi-walled carbon nanotubes exhibited better conductivity retention after friction. Therefore, the main technical advantage of the composite of single-walled and multi-walled carbon nanotubes in this invention lies in improving the continuity and stability of the conductive network after mechanical friction.

[0120] Experimental Example 3: Verification of Curing of Silicon-Containing Structures.

[0121] To verify the changes in the silicon-containing structure after the polysilazane resin participates in film formation, Fourier transform infrared spectroscopy was performed on the aqueous carbon nanotube coating liquid before curing and the carbon nanotube composite coating after curing in Example 1.

[0122] During the test, the main absorption peaks of the coating liquid before curing and the composite coating after curing were recorded respectively. The results are shown in the table below.

[0123] Pre-curing coating liquid 800~1200 Si—N 820~940 Pre-curing coating liquid 2100~2160 Si—H 2160 Pre-curing coating liquid 3200~3500 N—H 3250~3300 Composite coating after curing 1050~1120 Si—O—Si 1095 Composite coating after curing 800~1200 Si-N related networks 820~940 After curing, the composite coating is at 1095 cm. -1 The presence of Si-O-Si correlated absorption characteristics in the vicinity, along with Si-N correlated absorption characteristics, indicates the existence of a stable silicon-containing network structure in the composite coating after heat curing. Combined with the use of polysilazane resin in the formulation and the performance differences between Experiment 2 with and without polysilazane resin, these results demonstrate that polysilazane resin participates in the formation of the silicon-containing inorganic phase.

Claims

1. A high-hardness transparent conductive glass product, characterized in that, Includes a glass substrate and a carbon nanotube composite coating directly bonded to at least one surface of the glass substrate; The carbon nanotube composite coating comprises a silicon-containing inorganic phase, an organic resin phase, and a carbon nanotube conductive network. The silicon-containing inorganic phase is formed by curing polysilazane resin and is bonded to the surface of the glass substrate; The organic resin phase is formed from polyurethane-modified acrylate, epoxy acrylate, and silicone resin; The carbon nanotube conductive network includes single-walled carbon nanotubes and multi-walled carbon nanotubes, and the single-walled carbon nanotubes and multi-walled carbon nanotubes overlap each other to form a conductive path. The silicon-containing inorganic phase and the organic resin phase together fix the carbon nanotube conductive network.

2. The high-hardness transparent conductive glass product according to claim 1, characterized in that, The mass ratio of the polyurethane modified acrylate, polysilazane resin, epoxy acrylate and silicone resin, based on the mass of the resin stock solution, is (8-12):(12-15):5:3; the silicone resin is a polyorganosiloxane with a cross-linked network structure.

3. The high-hardness transparent conductive glass product according to claim 1, characterized in that, The mass ratio of the single-walled carbon nanotubes to the multi-walled carbon nanotubes is 3 to 5:1; the diameter of the single-walled carbon nanotubes is 1 to 3 nm, and the diameter of the multi-walled carbon nanotubes is 5 to 30 nm.

4. The high-hardness transparent conductive glass product according to claim 1, characterized in that, No separate organic undercoat is provided between the glass substrate and the carbon nanotube composite coating, and the dry film thickness of the carbon nanotube composite coating is 2 to 4 μm.

5. The high-hardness transparent conductive glass product according to claim 1, characterized in that, The high-hardness transparent conductive glass product has a light transmittance retention rate of no less than 98% relative to the uncoated glass substrate, a haze of no more than 1%, and a sheet resistance of no more than 9 × 10⁻⁶. 6 Ω / □, and the pencil hardness measured under a 750 g load is not less than 3 H.

6. A method for preparing a high-hardness transparent conductive glass product, characterized in that, Includes the following steps: S1. Mix and grind single-walled carbon nanotubes and multi-walled carbon nanotubes. Add the ground carbon nanotube material and dispersant to deionized water for the first ultrasonic dispersion. Then centrifuge and collect the supernatant to obtain carbon nanotube dispersion. S2. Add film-forming agent and additive to the carbon nanotube dispersion and perform a second ultrasonic dispersion to obtain an aqueous carbon nanotube coating solution; The film-forming agent includes polyurethane-modified acrylate, polysilazane resin, epoxy acrylate, and silicone resin. S3. The aqueous carbon nanotube coating liquid is directly coated onto at least one side surface of the glass substrate to form a wet film; S4. After the wet film is surface-dried, it is heated and cured to form a silicon-containing inorganic phase of the polysilazane resin, and to form an organic resin phase of the polyurethane-modified acrylate, the epoxy acrylate, and the organosilicon resin. The silicon-containing inorganic phase and the organic resin phase together fix the carbon nanotube conductive network formed by the single-walled carbon nanotubes and the multi-walled carbon nanotubes, forming a carbon nanotube composite coating on the surface of the glass substrate, thereby obtaining a high-hardness transparent conductive glass product.

7. The method for preparing a high-hardness transparent conductive glass product according to claim 6, characterized in that, In S1, the mass ratio of the single-walled carbon nanotubes to the multi-walled carbon nanotubes is 3 to 5:1; The raw materials of the carbon nanotube dispersion include, by mass percentage, 0.01% to 1.5% carbon nanotube material, 0.1% to 8.5% dispersant, and the balance being deionized water; The grinding time is 3 to 8 hours, the power of the first ultrasonic dispersion is 250 to 400 W, and the time of the first ultrasonic dispersion is 15 to 60 minutes.

8. The method for preparing a high-hardness transparent conductive glass product according to claim 6, characterized in that, In S2, the additives include wetting agents, leveling agents, defoamers, and thickeners; based on the mass of the carbon nanotube dispersion, the amount of film-forming agent added is 10% to 40% of the mass of the carbon nanotube dispersion, the amount of wetting agent added is 0.1% to 1.8%, the amount of leveling agent added is 0.05% to 0.6%, the amount of defoamer added is 0.01% to 0.3%, and the amount of thickener added is 0.05% to 0.1%. The mass ratio of the polyurethane modified acrylate, the polysilazane resin, the epoxy acrylate, and the silicone resin, based on the mass of the resin stock solution, is (8-12):(12-15):5:

3. The power of the second ultrasonic dispersion is 250-400 W, and the time of the second ultrasonic dispersion is 15-30 min.

9. The method for preparing a high-hardness transparent conductive glass product according to claim 8, characterized in that: The wetting agent is an anionic modified polyether silicone wetting agent or an alkyl sulfonate wetting agent; The leveling agent includes at least two types of silicone-based leveling agents; The defoamer is an organosilicon defoamer or a polyether-modified organosilicon defoamer; The thickener is an aqueous thickener of polyacrylate or sodium polyacrylate.

10. The method for preparing a high-hardness transparent conductive glass product according to claim 8, characterized in that: In S1, based on the total mass of the raw materials used to prepare the carbon nanotube dispersion, the mass percentage of the carbon nanotube material is 0.5%, the mass percentage of the dispersant is 5%, the mass ratio of the single-walled carbon nanotubes to the multi-walled carbon nanotubes is 4:1, the grinding time is 6 h, the power of the first ultrasonic dispersion is 360 W, and the time of the first ultrasonic dispersion is 45 min. In S2, based on the mass of the carbon nanotube dispersion, the amount of film-forming agent added is 35%, the amount of wetting agent added is 1%, the amount of leveling agent added is 0.3%, the amount of defoamer added is 0.15%, the amount of thickener added is 0.05%, the power of the second ultrasonic dispersion is 360 W, and the time of the second ultrasonic dispersion is 30 min; In S3, the thickness of the wet film is 6 μm; In S4, the wet film is surface-dried at 25°C for 5 min, and then cured at 120°C for 20 min to form a carbon nanotube composite coating. The dry film thickness of the carbon nanotube composite coating is 2–4 μm.